Epidermal growth factor or transforming growth factor alpha is required for kidney tubulogenesis in matrigel cultures in serum-free medium. - Taub, M (1990)
The ability of matrigel, a reconstituted basement membrane gel, to induce the differentiation of baby mouse kidney cells has been examined in a hormonally defined serum-free medium. Primary cultures of baby mouse kidney cells were observed to form tubules over a time interval of 1-2 weeks in matrigel. Electron microscopic studies showed that tubules with lumens were present, and the tubule morphology was similar to that of the collecting duct. When using matrigel from which the growth factors had been removed, tubule formation no longer occurred, unless the medium was further supplemented with epidermal growth factor (10 ng/ml). Transforming growth factor alpha stimulated tubule formation as effectively as epidermal growth factor, whereas transforming growth factor beta had an inhibitory effect on tubule formation. These data suggest that both an extracellular matrix and specific growth factors may regulate kidney differentiation during development.